Idiopathic pulmonary fibrosis and GERD: links and risks - Ghisa, Matteo (Ther Clin Risk Manag, 2019)
Gastroesophageal reflux disease (GERD) and idiopathic pulmonary fibrosis (IPF) are two pathological conditions often strictly related, even if a clear relationship of causality has not been demonstrated. GERD is a frequent comorbidity in IPF patients, as demonstrated using combined multichannel intraluminal impedance-pH, despite being mostly clinically silent. According to that, it has been hypothesized that microaspiration of gastric material may play a fundamental role in the fibrotic transformation of pulmonary parenchyma. In contrast, it cannot be excluded that IPF may favor GERD by increasing the negative intrathoracic pressure. Therefore, this relationship is uncertain as well as not univocal. Nevertheless, the latest international guidelines recommend the use of proton pump inhibitors (PPIs) in IPF based on several data showing that PPIs can stabilize lung function, reduce disease flares and hospitalizations. On the contrary, recent studies not only question the relevance of these results, but also associate the use of PPIs with an increased risk of lung infections and a negative prognostic outcome. The aim of this review is to analyze the possible links between GERD and IPF and their possible therapeutic implications, trying to translate this scientific evidence into useful information for clinical practice.